Peran Mediasi Brand Ambassador pada Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian - R. Neny, Kusumadewi; Suparto LM, L; Rusdiana, Alan; Pradilla, Mora (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
The large number of cosmetic industries that are emerging at the moment, one of which is hand body lotion products for body skin care, means that consumers have many considerations in purchasing decisions, consumers tend to have more importance in terms of quality and in terms for promotion through brand ambassadors which are very intensively carried out. purchasing decisions continue to increase. Purpose of the search is to determint various factors that influencer product price and quality for buying decisions mediated by the Ambassador brand. Research using survey method and a descriptive verification approach. Data collection techniques use was use a questionnaire. Population in this research is consumers of Scarlett hand body lotion products in Majalengka Regency and a sample 120 respondents. The tools SmartPLS analysis. Research outcome found that price have significant positive influencer for buying decisions. The quality of product positive and significant influence buyer resolve. Brand Ambassadors have positive and significant influence on buying decisions. Price positive but not significant effect on brand awareness. Product quality positive and significant effect on the Ambassador brand. Price on purchasing decisions mediated by the Ambassador brand has positive but not significant effect. Product quality for buying decisions is mediated by Ambassador brand and positive significant effect.